PERILAKU DAN POLA MAKAN IBU DALAM MASA NIFAS: GAMBARAN KEMISKINAN KESEHATAN REPRODUKSI DI WILAYAH PUSKESMAS I KECAMATAN GUNTUR KABUPATEN DEMAK. - Edy Wuryanto; Eny Winaryati (JURNAL LITBANG, 2007)
WHO calculates 500.000 people died because of pregnancy and delivery process every year, 99% occures in developed countries, and 50o/o of them are in Indonesia- This is mainly caused by postpartum bleeding and bad malnutritions. To decrease the risk factoi of death, we have to fulfill the need of nutritions, especially iron, and optimilize health iervice given. Research about type of food consumption, Hb level, and purperalmother habbit, as description of reproduction health poverity in Public Health Service sector I Guntur-Demak, with the lowest level of KIA, become so important. From 65 purperal mothers as noted, there are 4 antenatal examinations, it meons that we have enough case data with 100% TT immunization, which most of them are executed by mtdide (84,60/0), dukun (1,5%o), doctor (12,3%o); 6 of them with caesar process. Most of postpartum examination hold by midwife, it is because of midwife active visit rate '(81,'5%o). All pusperal mother agreed to follow family planning (KB) programe, which most chpotri Kn epe is syringe (52,3%o), most of them followed their neighbour suggestion (35,4%o).-Deating withfirst mother milk (ASI) supply, 92,3% are suggestedby the midwife.Will-to supply ASI by themselves is good (81%o), but still without good planning of time (52,5%o).-Food consumption rate of purperal mother still low, it can be shown iince most of them neyer consume animal protein (78,5%o), so that, most of them are also never eat vigetables (58,5%o). This is why they have Hb level 7-8 gr% (86,2%o). In fact, heme iron (ix. meat) is well absorbed than non-heme iron. This also suported by factsthat there are some restrictions from their tradisional culture which are condirably taboo. From the data above, there are some recommendations asfollows: It is important to give a good explanation about health and nutritions to society which help them to get colrect iiformation from the expert by managing human resources; It is important for purperal mother to consume Fe tablet, since there are lot of them having anemia; It isimjortant to socialize garden and farming reconstruction to fuffill family need oJ nutrition.Key words; postpartum, purperal mother, malnutritions, nutrition.